2018
DOI: 10.1101/342915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota Diversity across Ethnicities in the United States

Abstract: 32Composed of hundreds of microbial species, the composition of the human gut 33 microbiota can vary with chronic diseases underlying health disparities that 34 disproportionally affect ethnic minorities. However, the influence of ethnicity on the gut 35 microbiota remains largely unexplored and lacks reproducible generalizations across 36 studies. By distilling associations between ethnicity and differences in two United States 37 based 16S gut microbiota datasets including 1,673 individuals, we report 12 mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 79 publications
1
62
0
2
Order By: Relevance
“…The NHBCS includes primarily White women and their infants from New Hampshire and Vermont in the United States. Thus, our results may not be generalizable to other communities with different ethnic [50] or geographic compositions [30]. Most variables were collected via standardized medical record review including age, sex, delivery mode, and antibiotic exposures reducing multiple possible biases.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…The NHBCS includes primarily White women and their infants from New Hampshire and Vermont in the United States. Thus, our results may not be generalizable to other communities with different ethnic [50] or geographic compositions [30]. Most variables were collected via standardized medical record review including age, sex, delivery mode, and antibiotic exposures reducing multiple possible biases.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…Ethnicity differences, though often overlooked in studies, are known to affect hypercholesterolemia and CAD development. Ethnicity differences can capture biological variations derived from social, economic, and cultural differences, human genetic variation, and biogeographical ancestry divergences, as well as lifestyle and dietary differences [183]. Risk factors of CAD development including smoking, blood pressure, obesity, and cholesterol can also vary among different ethnicity groups [184,185], resulting in certain groups having an earlier onset and worse outcomes of CAD.…”
Section: Microbiota Demographic Factors and Cadmentioning
confidence: 99%
“…In addition, African Americans also have a diet with relatively higher sugar, higher sodium, and lower potassium [187] contents that can lead to higher blood pressure. In addition, ethnicity and dietary differences are associated with variations in microbial composition and abundance [181,189,190] and even more strongly with gut microbiota than other factors such as genetics [191], age, sex, and BMI [183]. For example, comparative studies of the microbiome in rural and urban areas in healthy individuals have reported that populations residing in non-Western and/or rural areas have a higher bacterial diversity when compared with populations in America and Europe [162,192].…”
Section: Microbiota Demographic Factors and Cadmentioning
confidence: 99%
“…In another approach, taxa can be categorized, or binned, by their phylogenetic relationships (e.g. all taxa that share a family are analyzed as one unit) (37,38). Such binning methods may obscure meaningful biological signal, and are also heavily database dependent not all microbes are clearly classified by taxonomy.…”
Section: Current Methods For Dimensionality Reductionmentioning
confidence: 99%